COLLAPSE OF CAVES AT SHALLOW DEPTH IN GAZIANTEP CITY CENTER, TURKEY: A CASE STUDY - Canakci H. (My University, 2007)
This paper focuses on an investigation of the possible causes for the collapse of limestone caves in Gaziantep, Turkey. The city contains a lot of man-made caves, at a shallow depth, of various width and length. These caves were mainly excavated to provide work or storage space. As the city has been growing fast with increased population, many structures were constructed over these caves. Recently, two caves collapsed and five houses were damaged. These caves are all made of limestone and it was observed after the collapse that the limestone was saturated with water due to sewer pipe leakage and surface water. Tests were carried out on the limestone and it was determined that the compressive strength of limestone decreases by about 50% and the tensile strength decreased by about 80% when saturated with water. It was concluded that the reduced strength of the limestone combined with additional loads due to the factors mentioned above seem to be the main reason for these collapses.
Keywords: LIMESTONE; SATURATION; ROCK MECHANICS; COMPRESSIVE STRENGTH; TENSILE STRENGTH